O uso de um livro-caderno de matemática alternativo em sala de aula: praticidade e coerência didática voltadas para a realidade local e tecnológica - FREIRE, Francielck Domingos (Instituto Federal do Amapá, 2021)
This paper analyzes two collections of textbooks in Mathematics adopted in recent years in the State School Esther da Silva Virgolino in Amapá, showing some educational use these collections to the disorders in the classroom, such as discrepancies between the contents of these collections and of course plane school, lack of objectivity as the approach of certain topics of mathematics and addictions in planning the content and exercises. For this analysis was used as a reference book Exam Texts: Analysis Math books for middle school LIMA et al, 2001 and of course plan adopted in school (divergent content present in current books). For this, there is a brief history of the textbook in Brazil, government programs (acquisition and quality of the books), analysis of collections and, finally, proposes the use of an alternative teaching material, it is possible to associate the mathematics content and local technological reality, bringing positive results for the teaching-learning process.